Immunomodulatory and Mechanistic Considerations of Hibiscus sabdariffa (HS) in Dysfunctional Immune Responses: A Systematic Review - Umeoguaju, Francis U.; Ephraim-Emmanuel, Benson C.; Uba, Joy O.; Bekibele, Grace E.; Chigozie, Nwondah; Orisakwe, Orish Ebere (Frontiers in Immunology, 2021)
Hibiscus sabdariffa calyx (HS) water decoction extract is a commonly consumed beverage with various pharmacological properties. The possible effect of HS intake on immune mediators is the thrust of this systematic review. Scopus and PUBMED databases were searched for all human and animal studies which investigated the effect of HS administration on immune related biomarkers. For each of the immune biomarker, the mean, standard deviation and number of subjects were extracted for both the HS treated and untreated group. These values were used in the computation of the standardized mean difference (SMD). Statistical analysis and forest plot were done with R statistical software (version 3.6.1). Twenty seven (27) studies met the eligibility criteria. Twenty two (22) of the studies were used for the meta-analysis which included a total of 1211 subjects. The meta-analysis showed that HS administration significantly lowered the levels of TNF-α (n=10; pooled SMD: -1.55; 95% CI: -2.43, -0.67; P < 0.01), IL-6 (n=11; pooled SMD:-1.09; 95% CI: -1.77, -0.40; P < 0.01), IL-1β (n=7; pooled SMD:-0.62; 95% CI: -1.25, 0.00; P = 0.05), Edema formation (n=4; pooled SMD: -2.29; 95% CI: -4.47, -0.11; P = 0.04), Monocyte Chemoattractant Protein -1 (n=4; pooled SMD: -1.17; 95% CI: -1.78, -0.57; P < 0.01) and Angiotensin converting enzyme cascade (n=6; pooled SMD: -0.91; 95% CI: -1.57, -0.25; P < 0.01). The levels of IL-10 (n=4; pooled SMD: -0.38; 95% CI: -1.67, 0.91; P = 0.56), Interleukin 8 (n=2; pooled SMD:-0.12; 95% CI: -0.76, 0.51; P = 0.71), iNOS (n=2; pooled SMD:-0.69; 95% CI: -1.60, 0.23 P = 0.14) and C- Reactive Protein (n=4; pooled SMD: 0.05; 95% CI: -0.26, 0.36; P = 0.75), were not significantly changed by HS administration. Some of the results had high statistical heterogeneity. HS may be promising in the management of disorders of hyperactive immune system or chronic inflammation.